Spin-wave propagation in metallic co25fe75 films determined by microfocused frequency-resolved magneto-optic kerr effect - Liensberger, Lukas; Flacke, Luis; Rogerson, David; Althammer, Matthias; Gross, Rudolf; Weiler, Mathias (IEEE Magnetics Letters, 2019)
We investigated the magnetization dynamics of a patterned Co25Fe75-based heterostructure with a novel optical measurement technique that we call microfocused frequency-resolved magneto-optic Kerr effect. We measured the magnetic field dependence of the dynamical spin-wave susceptibility and recorded a spatial map of the spin waves excited by a microwave antenna. We compare these results to those obtained on the same sample with the established microfocused Brillouin light scattering technique. With both techniques, we find a spin-wave propagation length of 5.6 μm at 10 GHz. We also measured the dispersion of the wave vector and the spin-wave propagation length as a function of the external magnetic field. These results are in good agreement with the existing literature and with the Kalinikos-Slavin model.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Magnetic films; Magnetic measurements; Magnetization dynamics; Magnonics; Microwave magnetics; Patterned materials; Spintronics